The Right of Management Originating from Indigenous People Ulayat Land: Determinant of Solution - Abdul Aziz, Gheovani; Suhariningsih, Suhariningsih; Sri Kawuryan, Endang (International Journal of Business, Law, and Education, 2024)
Indonesia has extensive forest areas and a rich diversity of cultures and customs. This is related to Indigenous Legal Communities, which, according to the Constitution, must be recognized and respected. This research aims to examine whether granting the Right of Management over Ulayat Land represents a solution for sustainable land management or whether it could be detrimental to the land rights of Indigenous Communities. This study employs a Normative Juridical approach, utilizing both a Legislative and Conceptual approach. The legal materials used in this research include Primary and Secondary Legal Materials, which are analyzed using a perspective analysis technique. The research findings indicate that granting the Right of Management over Ulayat Land held by Indigenous Legal Communities can positively impact sustainable land management, provided that Regional Regulations and Regional Decrees are in place to recognize and protect Indigenous Legal Communities. Conversely, it could be detrimental to the existence of Indigenous Communities if Regional Regulations and Regional Decrees concerning the recognition and protection of Indigenous Legal Communities are not properly regulated.